Effect of Low-Pressurized Perfusion with Different Concentration of Elastase on the Aneurysm Formation Rate in the Abdominal Aortic Aneurysm Model in Rabbits. (14th November 2016) - Nie, Maoxiao; Yan, Yunfeng; Li, Xinhe; Feng, Tingting; Zhao, Xin; Zhang, Mingduo; Zhao, Quanming
Abstract : Establishing an animal model of abdominal aortic aneurysm (AAA) is the key to study the pathogenesis and the pathophysiological features of AAAs. We investigated the effects of low-pressurized perfusion with different concentrations of elastase on aneurysm formation rate in the AAA model. Fifty male New Zealand white rabbits were randomly divided into A, B, C, D, and E groups. 10  μ L of normal saline was perfused into the abdominal aorta in group A and 1 U/mL, 10 U/mL, 100 U/mL, or 200 U/mL of elastase was, respectively, perfused for the other four groups. All the animals were perfused for 7 min. Doppler ultrasound examinations of the abdominal aorta were performed before surgery and on day 14 after surgery. The rabbits were sacrificed and the perfused segment of the abdominal aorta was observed visually and after staining. The aneurysm formation rate of group A, group B, group C, group D, and group E was, respectively, 0%, 0%, 33.3%, 102.5–146.8%, and 241.5–255.2%. The survival rate of five groups was 90%, 90%, 90%, 90%, and 40%, respectively. So, we concluded that low-pressurized perfusion with 100 U/mL of elastase can effectively establish AAAs in rabbits with a high aneurysm formation rate.